Answer:
3x^2 -4
Step-by-step explanation:
F(x)=2x^2+3 and g(x)=x^2-7
(f+g)(x) =
We add the two functions together
(f+g)(x) =2x^2+3+x^2-7
I like to line them up vertically
(f+g)(x) =
2x^2 +3
+x^2 -7
------------------
3x^2 -4
Answer:
The first one.
Step-by-step explanation:
The first one. 7x² times 2x = 14x³
Answer:
X = 11
Step-by-step explanation:
Simplifying
X + 24 = 35
Reorder the terms:
24 + X = 35
Solving
24 + X = 35
Solving for variable 'X'.
Move all terms containing X to the left, all other terms to the right.
Add '-24' to each side of the equation.
24 + -24 + X = 35 + -24
Combine like terms: 24 + -24 = 0
0 + X = 35 + -24
X = 35 + -24
Combine like terms: 35 + -24 = 11
X = 11
Simplifying
X = 11